Haematopoietic growth factors and their therapeutic use - Wadhwa, Meenu; Thorpe, Robin (Thrombosis and Haemostasis, 2008)
Haematopoietic growth factors constitute an important group of proteins that predominantly regulate the process of haematopoiesis. While some of these proteins have a very broad array of action on very early haematopoietic progenitors leading to multi-lineage increases in haematopoietic cell production and differentiation, others act in a restricted manner on specific committed terminally differentiated cell types. On the basis of their unique spectrum of activities, several factors are approved for clinical use in various indications while others are under investigation in the clinic either alone or as combination therapy. In this review, we have described factors which directly and in some cases indirectly influence haematopoiesis with particular focus on those factors which are either approved or show potential for clinical use. A brief description of the products that are currently available for clinical use is also provided. At present, several new products which include fusion proteins, peptide mimetics are either at the pre-clinical stage or in clinical development for various indications and these are also briefly described.
Keywords: Haematopoiesis; second-generation; biosimilars; stem cells; adverse